Case of mucoepidermoid carcinoma of the sublingual gland accompanied with extensive dystrophic calcification and intratumoral bone formation. Issue 11 (15th July 2015) - Maruse, Yasuyuki; Kawano, Shintaro; Kiyoshima, Tamotsu; Goto, Yuichi; Matsubara, Ryota; Chikui, Toru; Yoshiga, Daigo; Nakamura, Seiji; Andersen, Peter
Abstract Background Mucoepidermoid carcinoma (MEC) is the most common salivary gland malignancy. Although the histopathological findings are diverse, no case of salivary MEC accompanied with bone formation has been reported. Herein, we present the first case of MEC with intratumoral bone formation. Methods and Results A case of a 75‐year‐old female patient with an asymptomatic mass of the oral floor is presented. Enhanced CT revealed a tumorous mass with radiopaque materials in the oral floor. A pathological diagnosis of MEC was obtained by biopsy. Radical surgery was performed with the patient under general anesthesia. The resected specimen was finally diagnosed as MEC. Histopathologically, hyalinization, and dystrophic calcification were conspicuous within the stromal components of the tumor. Interestingly, ectopic bone formation was also found in the tumor tissues. Bony materials with osteocyte‐like cells were also observed in a series of dystrophic calcification. Conclusion These findings suggest that bony materials are associated with dystrophic calcification. © 2015 Wiley Periodicals, Inc. Head Neck 37: E161–E164, 2015